The purple acid phosphatase GmPAP17 predominantly enhances phosphorus use efficiency in soybean. (July 2022) - Xu, Huanqing; Zhang, Hengyou; Fan, Yukun; Wang, Ruiyang; Cui, Ruifan; Liu, Xiaoqian; Chu, Shanshan; Jiao, Yongqing; Zhang, Xingguo; Zhang, Dan
Abstract: Purple acid phosphatase (PAP) is an important plant acid phosphatase, which can secrete to the rhizosphere to decompose organophosphorus, promote phosphorus use efficiency, plant growth and development. However, little is known about the functions of intracellular PAP in plants, especially for soybean. Our previous study integrating QTL mapping and transcriptome analysis identified an promising low phosphorus (LP)-induced gene GmPAP17 . Here, we determined that GmPAP17 was mainly expressed in roots and had a strong response to LP stress. Furthermore, and the relative expression in the root of LP tolerant genotypes NN94–156 was significantly greater than that of LP sensitive genotype Bogao after LP stress treatment. The overexpression of GmPAP17 significantly enhanced both acid phosphatase activity and growth performance of hairy roots under LP stress condition, it was vice versa for RNAi interference of GmPAP17, indicating that GmPAP17 plays an important role in P use efficiency. Moreover, yeast two-hybrid and bimolecular fluorescence complementation analysis showed that GmRAP2.2 was involved in the regulation network of GmPAP17. Taken together, our results suggest that GmPAP17 is a novel plant PAP that functions in the adaptation of soybean to LP stress, possibly through its involvement in P recycling in plants. Highlights: A newly-identified gene, GmPAP17, significantly enhanced the tolerance to low P stress by enhancing root growth and P use efficiency. Overexpression of GmPAP17 significantly enhanced the tolerance to low P stress by enhancing root growth and P use efficiency. GmPAP17 regulates the response of soybean to low phosphorus stress by directly interacting with GmRAP2.2.